The Effect of Service Quality and Store Image on Customer Loyalty Mediated by Perceived Value and Customer Satisfaction at Indomaret Stores in Kediri City - Muttaqien, Zaenul; Widuri, Trisnia (Formosa Journal of Science and Technology, 2023)
This study analyses the effect of service quality and store image on customer loyalty mediated by perceived value and customer satisfaction. The data collection used questionnaires distributed to respondents who shopped at Indomaret stores in Kediri City. The population in this study were all consumers who shopped at Indomaret stores in Kediri city. The number of samples in this study were 100 respondents. The data analysis used SmartPLS 3.0 software using a variant-based SEM approach which presents the outer model test and inner model test. The outer model test is used to specify the relationship between latent variables and their indicators and the inner model test is used to predict the relationship between latent variables.